Effects of acute aerobic and resistance exercise on executive function: An ERP study. Issue 12 (December 2019) - Wu, Chih-Han; Karageorghis, Costas I.; Wang, Chun-Chih; Chu, Chien-Heng; Kao, Shih-Chun; Hung, Tsung-Min; Chang, Yu-Kai
Abstract: Objectives: This study addressed the effects of acute, moderate-intensity aerobic and resistance exercise on the shifting aspect of cognition following a 30-min recovery period. It also explored the neuro-electrical activation that underlies the relationship between acute exercise and cognitive function through the examination of P3b and N1 components of event-related potentials. Design: A counterbalanced, repeated-measures experimental design. Methods: Thirty-five volunteer young adults completed two experimental sessions (i.e., acute aerobic exercise (AE) and resistance exercise (RE), matched in terms of intensity, and one reading session (control). The AE entailed cycling at 60–70% of maximal heart rate reserve for 30 min. In the RE session, participants performed seven exercises with two sets of 8–12 repetitions at 70% of 10-repetition maximum. Each participant's neuro-electrical activation was recorded 30 min after each session while s/he completed the task-switching test. Results: After the 30-min recovery period, both AE and RE elicited shorter response times in global switching ( η p 2 = 0.24 ) and local switching ( η p 2 = 0.16 ) were observed when compared to control. Additionally, larger P3b amplitudes (but not N1 amplitudes) were evident in global switching ( η p 2 = 0.15 ) and local switching ( η p 2 = 0.16 ), regardless of exercise modality. Conclusions: The present findings suggest that acute exercise has positive effects on cognitive function. Exercise-induced alterations during the later stages of mental processing might result in superior performance. There were significant selective benefits in terms of brain function regardless of exercise modality.